A study of wound infections and its antibiogram in surgical intensive care unit of a tertiary care hospital - Dr. Upasana Bhumbla; Dr. Safaa Muneer Ahmed; Dr. Dinesh Raj Mathur; Dr. A.S. Dalal (Tropical Journal of Pathology and Microbiology, 2019)
Background: Wound infections can be caused through two major sources: exogenous and endogenous bacteria. The probability of wound infection largely depends on the patients systemic host defenses, local wound conditions and microbial burden. Despite modern surgical techniques and the use of antibiotic prophylaxis, Surgical Site Infection (SSI) is one of the most common complications encountered in surgery. SSI places a significant burden on both the patient and health system. SSI is thus a major cause of morbidity, prolonged hospital stay and increased health costs. Objective of this study was to identify and isolate various bacteria from wound infections in a surgical intensive care unit and to study their antibiogram. Methods: Two wound swabs were collected from the wound and from a drop of aspirate, smear was made on clean glass slide and Gram staining was done for direct microscopic examination under oil immersion 100X objective to know various morphological types of bacteria and presence or absence of inflammatory cells. Second swab/drop of aspirate was used for culture by inoculating it on routine media like Blood Agar, Nutrient Agar and Mac Conkeys agar, incubated at 37° C for 24 hours aerobically. Result: Out of 238 pus samples, 209 (88.6%) were culture positive for bacterial growth and no growth was observed in 29(12.4%) cases. Out of 209 bacterial culture positive cases, 201 were monobacterial and 8 were poly bacterial. Out of 201 bacterial isolates; S. aureus (56/26.6) was the commonest followed by P. aeruginosa (47/22.4%). Conclusion: The study concludes that variety of aerobic bacteria is responsible for wound infection with predominance of Staphylococcus aureus followed by Pseudomonas aeruginosa